Effects of Ramadan Fasting on Recovery Following a Simulated Soccer Match in Professional Soccer Players: A Pilot Study - Bouzid, Mohamed Amine; Abaïdia, Abd-Elbasset; Bouchiba, Mustapha; Ghattassi, Kais; Daab, Wael; Engel, Florian A.; Chtourou, Hamdi (Frontiers in Physiology, 2019)
Objectives: Assessing the effects of Ramadan fasting on recovery following a soccer match simulation. Methods: Eight elite soccer players (age: 21.0 ± 0.4 years) performed a modified Loughborough Intermittent Shuttle Test protocol (LISTmod) on two occasions: 1 week before (BR) and during the fourth week of Ramadan (End-R). At BR and End-R, soccer players performed squat jump, countermovement jump, maximal voluntary contraction, and 20 m sprint, and creatine kinase, uric acid, and subjective ratings (feelings scale, quality of sleep, fatigue, muscle soreness and stress) were assessed at baseline and 0, 24, 48, and 72 h following LISTmod. Results: Following LISTmod, performance in squat jump (48 and 72 h) (p < 0.05), countermovement jump (48 and 72 h), maximal voluntary contraction (0, 24, 48, and 72 h), and 20 m sprint (0 and 48 h) decreased significantly on both occasions. Decreases were higher at End-R than BR. Creatine kinase levels increased significantly at 24 and 48 h at BR and End-R (p < 0.05). Uric acid increased at 0 and 24 h only on BR. Muscle soreness increased throughout the recovery period at both occasions, with a higher level at End-R. Stress rating increased only at 0 h on End-R, while fatigue rating increased at 24 h at BR and at 0, 24, and 48 h at End-R. Conclusion: Perturbations in physical performance and subjective ratings parameters were higher at the end of Ramadan. However, the results of this study showed that Ramadan fasting did not adversely affect the recovery following soccer match simulation in professional soccer players.